Garbhagriha (Sanctum Sanctorum) - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum), square in shape from the inside, features a distinct round or ghata (pot-shaped) linga, from which the temple derives its name, Ghateshvara. On the rear wall, a niche with an udgama (pediment of interconnected chaitya dormers) is fixed, housing a figure of a deity (currently without a head). Adjacent to it is another sculpture of a four-armed Goddess. The sculpture of this Goddess may belong to a later period, as her appearance differs from other sculptures in the temple.